Effect of die-casting cooling rate on the chemical conversion treatments of AZ91D magnesium alloy. (1st November 2016) - Hu, Lifang; Chen, Daming; Shi, Fangrong; Chen, Shaoping; Meng, Qingsen
Abstract: Temperature distribution of the thin-walled AZ91D magnesium components during die-casting process was simulated. The surface and cross-section microstructure investigations indicated that α -phase tended to grow up at the location with a low-cooling rate. Effect of die-casting cooling rate on the chemical conversion treatments of AZ91D magnesium alloy was characterised by means of scanning electron microscopy and glow discharge optical emission spectroscopy. The electrochemical reaction process of the chemical conversion treatments was investigated explicitly. Salt spray and potentiodynamic polarisation test results indicated that the coating formed at the location with a low-cooling rate had a poor corrosion resistance.